Adolescent Blood Pressure and the Risk for Early Kidney Damage in Young Adulthood. Issue 5 (7th March 2022) - Tsur, Avishai M.; Akavian, Inbal; Derazne, Estela; Tzur, Dorit; Vivante, Asaf; Grossman, Ehud; Rotem, Ran S.; Fishman, Boris; Afek, Arnon; Coresh, Josef; Chodick, Gabriel; Twig, Gilad
Abstract : Background: Recent guidelines classified blood pressure above 130/80 mm Hg as hypertension. However, outcome data were lacking. Objective: To determine the association between blood pressure in adolescence and the risk for early kidney damage in young adulthood. Methods: In this nationwide cohort study, we included 629 168 adolescents aged 16 to 20 who underwent medical examinations before mandatory military service in Israel. We excluded 30 466 adolescents with kidney pathology, hypertension, or missing blood pressure or anthropometric data at study entry. Blood pressure measurements at study entry were categorized according to the Clinical Practice Guideline for Screening and Management of High Blood Pressure in Children and Adolescents: group A (<120/<80 mm Hg; Reference group), group B (120/<80–129/<80 mm Hg), group C (130/80–139/89 mm Hg), and group D (≥140/90 mm Hg). Early kidney damage in young adulthood was defined as albuminuria of ≥30 mg/g with an estimated glomerular filtration rate of 60 mL/(min·1.73 m 2 ) or over. Results: Of 598 702 adolescents (54% men), 2004 (0.3%) developed early kidney damage during a mean follow-up of 15.1 (7.2) years. The adjusted hazard ratios for early kidney damage in blood pressure group C were 1.17 (1.03–1.32) and 1.51 (1.22–1.86) among adolescents with lean (body mass index <85th percentile) and high body mass index (body mass index ≥85th percentile), respectively. Corresponding hazard ratios for kidney disease in group D were 1.49 (1.15–1.93) and 1.79 (1.35–2.38) among adolescents with lean and high body mass index, respectively. Conclusions: Blood pressure of ≥130/80 mm Hg was associated with early kidney damage in young adulthood, especially in adolescents with overweight and obesity.